2019
DOI: 10.7759/cureus.3920
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oculomotor Nerve Palsy Caused by Compression from an Aberrant Posterior Communicating Artery

Abstract: Oculomotor nerve palsy (ONP) is a rare neurological deficit associated with numerous underlying pathologies. Of these, aneurysm of the posterior communicating artery (PCOM) has been described due to the intimate association with the third cranial nerve in the basal cistern. Less described are other vascular abnormalities and their contribution to ONP. We describe a case of ONP thought to result from a PCOM aneurysm, per the associated magnetic resonance imaging (MRI) scan, yet found intraoperatively to be caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…A study conducted by Krayenbuhl et al [ 14 ] suggested that in about 55% of elderly patients, the PCA was a “curve” that generally develop to tortuosity and dilation, which easily leads to neurovascular conflict. Secondly, the ON originates from the midbrain and traverses between the PCA and the SCA, then runs parallelly to the PcomA[ 15 ]. So, the ON often contacts the medial trunk of the PCA when it travels to the interpeduncular fossa, while the SCA spreads out beneath the oculomotor nerve and has little contact with the nerve[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Krayenbuhl et al [ 14 ] suggested that in about 55% of elderly patients, the PCA was a “curve” that generally develop to tortuosity and dilation, which easily leads to neurovascular conflict. Secondly, the ON originates from the midbrain and traverses between the PCA and the SCA, then runs parallelly to the PcomA[ 15 ]. So, the ON often contacts the medial trunk of the PCA when it travels to the interpeduncular fossa, while the SCA spreads out beneath the oculomotor nerve and has little contact with the nerve[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCA aneurysms are the most common types of aneurysms to form in the basal cistern and frequently involves in isolated OMNP due to their anatomical location. 14,15 The oculomotor nerve originates from the midbrain on the medial side of the cerebral peduncles and extends forward and laterally between the posterior cerebral artery and superior cerebellar artery. 15 Our patients presented with OMNP as result of compression by an aneurysm at the bifurcation of PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the intraocular muscular involvement during OMNP, pupillary involvement is also higher suspicion of compression because the pupillomotor fibers and their vascular component originates from overlying pia course along the superficial as well as superomedial aspect of the oculomotor nerve. 14,16 Also, trauma, stroke, post-surgical inflammation, neoplasms as well as microvascular damage from chronic disease have been implicated as cause of OMNP. 14,17 Our patient condition was initially misdiagnosed as an acute cerebral infarction and treated with aspirin, clopidogrel, fluvastatin and mecobalamin with no improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular etiology for cranial neuropathy encompasses a wide range of pathophysiology ranging from extrinsic compression, such as due to an aneurysm or coursing artery or due to ischemia from thrombosis. Posterior communicating artery aneurysm is a common etiology causing oculomotor nerve palsy, which can develop directly via mass effect of the growing aneurysm or indirectly after rupture of the aneurysm and adjacent clot formation 26. In addition, multiple cranial neuropathies can result from carotid cavernous fistula (CCF) and cavernous sinus thrombosis (CST), which can lead to CN III, IV, V1, V2, and VI polyneuropathy.…”
Section: Vascular Pathologymentioning
confidence: 99%